Occupational Health Related Publications in India: A bibliometric Analysis of Journals - Nalini, J. K. (Journal of Information and Knowledge, 2014)
A total of 31 articles on occupational health related problems studied in India, published in journals (both Indian and foreign) during the year 2000, having 533 citations were collected and analysed. It was observed that these studies were mostly contributed both by academic institutions and the research institutes, the former’s share being higher than that of latter. The number of publications on health consequences of chemical and textile workers topped the list with respiratory problems being predominant area of study. Most of the articles appeared in Indian journals and the Indian Journal of Occupational and Environmental Medicine was found to be the most preferred journa1. Majority of the publications came from a teamwork of 2-3 authors. On an average, a publication contained 5 pages. Analysis of references showed that the citations ranged from 2 to 73, with the oldest being for the year 1916. Most of the references (85%) spanned over the years 1970-1999. 68% of them having been referred to journals and 11.63% of the journals were Indian.